Bone regenerative effect of aqueous Cynanchum wilfordii extract in receptor activator of nuclear factor-κB ligand-induced osteoclast differentiation and estrogen deficiency-induced osteoporosis - Woojin Jun; Chul-yung Choi; Gyuok Lee; SangO Pan; Jaeyong Kim (International Journal of Phytomedicine, 2017)
Osteoporosis increases with age, most frequently in postmenopausal women because of reduced ovarian hormone levels. Furthermore, estrogen deficiency impairs trabecular metaphyseal bone. Although efficacious, long-term hormone replacement therapy (HRT) has estrogen-like side effects including breast and endometrial cancers, and non-hormonal or herbal therapies may be safer alternatives. Therefore, the aim of this study was to investigate the effects of aqueous extracts of Cynanchum wilfordii (CWW) on receptor activator of nuclear factor-κ B (NF-κ B) ligand (RANKL)-induced osteoclast differentiation in vitro and ovariectomy-mediated osteoporosis in vivo. CWW inhibited RANKL-induced osteoclast formation and tartrate-resistant acid phosphatase (TRAP) activity in primary mouse bone marrow-derived cells. We investigated the osteoprotective effect of CWW in an ovariectomized (OVX) Sprague-Dawley rat model treated with vehicle (OVX/vehicle), 17β-estradiol (OVX/E2), or three CWW doses (100, 200, and 400 mg/kg). After a 24-week treatment, the body and uterus weights were not affected except in the OVX/E2 group. Additionally, bone mineral density (BMD) and histological analyses showed that the BMD of the femurs of CWW400-treated rats was significantly higher than that of the OVX/vehicle rats, and comparable to that of the OVX/E2 group rats. Serum levels of bone turnover markers alkaline phosphatase (ALP), osteocalcin, collagen type I C-telopeptide, and TRAP significantly decreased in the CWW400 group. Our results show that compared to the vehicle, CWW had a significant anti-osteoporotic effect in the OVX model. Taken together, CWW exhibited inhibitory effects on osteoclastogenesis in vitro, and we confirmed its in vivo efficacy in the prevention of osteoporosis.